POLA ASUH ANAK PADA IBU PEKERJA PABRIK DALAM PERSPEKTIF FIQIH PARENTING - Syamsuri Syamsuri (Jurnal Harkat : Media Komunikasi Gender, 2019)
Abstract. This paper examines child parenting that occurs in working mothers in Paiton Probolinggo, East Java. On the one hand, the demands of fulfilling the family economy forced the mothers to work hard outside the home. On the other hand, they are required to care for and assist children in proper parenting intensely. Based on this fact, it is necessary to study how changes in parenting happened to work mothers and how fathers and mothers worked together in families to do co-parenting. These two problems are then examined from a gender mainstreaming perspective and then analyzed through fiqh so that the concept of gender relations in parenting can be found in accordance with the values of Islamic teachings. Through a case study approach, collecting, processing, and analyzing data with qualitative research principles, this study resulted in the finding of delegating parenting from parents to others resulting in low-quality supervision and assistance from caregivers to children and low levels of child satisfaction. This study also found no occurrence of parenting that involved fathers and mothers in the principle of partnership and ignorance. In the perspective of parenting fiqh, the parenting patterns that occur in Paiton Probolinggo are not in accordance with the values and laws of parenting fiqh. Abstrak. Tulisan ini mengkaji tentang pola asuh anak yang terjadi pada ibu pekerja di Paiton Probolinggo Jawa Timur. Di satu sisi tuntutan pemenuhan ekonomi keluarga memaksa para ibu untuk bekerja keras di luar rumah. Di sisi yang lain mereka dituntut untuk secara intens merawat dan mendampingi anak dalam pola asuh yang tepat. Berdasarkan fakta ini, perlu dikaji bagaimana perubahan pola asuh yang terjadi pada ibu pekerja serta bagaimana kerjasama ayah dan ibu dalam keluarga melakukan coparenting. Kedua permaslahan tersebut selanjutnya dikaji dari perspektif gender mainstreaming untuk kemudian dianalisis melalui fiqih sehingga dapat ditemukan konsep relasi gender dalam pengasuhan anak yang berkesesuain dengan nilai nilai ajaran Islam. Melalui pendekatan case study, mengumpulkan, mengolah, dan menganalisis data dengan prinsip-prinsip penelitian kualitatif, kajian ini menghasilkan temuan adanya pendelegasian pola asuh anak dari orang tua kepada orang lain yang berakibat rendahnya mutu pengawasan dan pemdampingan dari pengasuh terhadap anak serta rendahnya tingkat kepuasan anak. Kajian ini juga menemukan tidak terjadinya coparenting yang melibatkan ayah dan ibu dalam prinsip kemitraan dan kesalingan. Dalam perspektif fiqih parenting, pola pengasuhan anak yang terjadi di Paiton Probolinggo ini tidak sesuai dengan nilai dan prinsip fiqih parenting.